Application of finite difference method in MHD differential type fluid flow in rotating frame - Mahadi, Shafaruniza (American Institute of Physics, 2014)
The research is focused on the problem relating to non-Newtonian fluid. The paper will highlight a differential type of fluid which include third grade and fourth grade fluids. The effect of material parameters of third and fourth grades fluids and rotation upon the velocity is discussed. The nonlinear problem is numerically solved by finite difference method. We discuss the consequence of material parameters for third and fourth grade fluids and rotation on the velocity profile.